Evaluasi Komparatif Algoritma Decision Tree, Random Forest, dan XGBoost untuk Software Defect Prediction Menggunakan Dataset NASA Software Metrics - Okky Prasetia; Syaeful Machfud (Forum Kerjasama Pendidikan Tinggi, 2026)
Software Defect Prediction (SDP) has become an important approach for identifying software modules that are likely to contain defects during the early stages of software development. However, the performance of prediction algorithms remains highly dependent on dataset characteristics, and no single algorithm has consistently demonstrated superior performance across different datasets. In addition, the use of synthetic datasets in SDP research still requires empirical validation to ensure that their characteristics remain representative of benchmark datasets such as the NASA Metric Data Program (NASA MDP). Therefore, this study aims to compare the performance of Decision Tree, Random Forest, and XGBoost using the Playground Series Season 3 Episode 23 dataset, a synthetic dataset developed based on the characteristics of the NASA MDP dataset. Prior to model training, the dataset underwent preprocessing, including missing value imputation, label encoding, and feature standardization. Model performance was evaluated using 10-fold stratified cross-validation with Accuracy, F1-Score, and AUC-ROC as the primary evaluation metrics. The experimental results indicate that ensemble learning methods achieved competitive performance compared with the single-classifier approach. Random Forest achieved the highest Accuracy of 0.8144, while XGBoost obtained the highest AUC-ROC score of 0.7929, indicating strong capability in distinguishing between defective and non-defective software modules on the evaluated dataset. Furthermore, feature importance analysis identified Lines of Code (LOC), Cyclomatic Complexity, Halstead Volume, IOCode, and branchCount as the most influential factors affecting software defect prediction. Based on the experimental results obtained from the selected dataset, the ensemble learning approach demonstrated competitive predictive performance and may be considered a promising alternative for developing Software Defect Prediction models. Nevertheless, the selection of the most appropriate algorithm should remain dependent on dataset characteristics and specific implementation requirements